Identification of Scientific Knowledge of The Process Making Palm Sugar as Local Wisdom of Banyumas and Its Potential for Empowering Scientific Thinking Skills - Jannah, Zayyana Finaul; Suciati*, Suciati; Fakhrudin, Isma Aziz; Silvita, Silvita; Prasetyo, Opik; Rachman, Hening Triandika (Universitas Syiah Kuala, 2024)
Students' lack of knowledge regarding local wisdom, especially the process of making palm sugar, can result in the loss of national identity. Students' relatively low scientific thinking skills can cause students to have difficulty filtering relevant information and global issues, this will also have an impact on the fading of local wisdom with modernization and the flow of globalization. Apart from that, the teacher's lack of information regarding scientific knowledge in the process of making palm sugar means that the integration of local wisdom in science learning is not yet optimal and learning is still theoretical. This research aims to: (1) identify scientific knowledge in the process of making palm sugar as local wisdom in Banyumas; and (2) analyzing the potential of scientific knowledge in the process of making palm sugar to empower students' scientific thinking skills. This research is a descriptive qualitative research. The data sources include informants and relevant journals. The sampling technique uses purposive sampling. Data collection was carried out through interviews, observation and documentation methods. The data validity technique uses triangulation techniques. The data analysis technique uses interactive analysis. The results of this research show that the process of making palm sugar contains scientific knowledge consisting of three aspects, namely biology, physics and chemistry. Scientific knowledge in the process of making palm sugar has the potential to empower scientific thinking skills which include 4 aspects, namely inquiry, analysis, inference and argument